UPPER JURASSIC RADIOLARIANS FROM INICI MOUNTAIN AREA (NORTHWESTERN SICILY, ITALY): BIOCHRONOLOGY AND CALIBRATION BY AMMONITES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
This research is devoted to the biostratigraphic analysis of radiolarian assemblages of the Upper Jurassic intermediate siliceous member of the Rosso Ammonitico Formation in the Inici Mountain area (Northwestern Sicily, Italy). The aims of this paper are to give the first description of this radiolarian associations, to establish a direct biochronostratigraphy by means of radiolarians, and to calibrate radiolarian biozones by ammonite zones. During Late Jurassic time, Inici Mt. area was part of a submerged pelagic plateau characterized by deposition of Rosso Ammonitico condensed facies (Rosso Ammonitico Inferiore -RAI- and Rosso Ammonitico Superiore -RAS-) and basinal facies (Rosso Ammonitico Medio -RAM-). Four stratigraphical sections from the RAM have been studied: Fornazzo Strada, Fornazzo Cava, Castello Inici and Balada di Baida. In all sections RAM consists of siliceous nodular limestone alternating with marly limestone, and moderately preserved radiolarians. Biostratigraphic correlation has been made using the Unitary Associations (UAs) method: 11 UAs have been identified and grouped in 5 biozones (Unitary Associations Zones: UAZs) whose age is calibrated by ammonites found in the same successions and/or in the under- and overlying formations. Ammonite assemblages assign the top of RAI to mid Oxfordian and the top of RAM to upper Kimmeridgian. The ranges of Eucyrtidiellum unumaense (Yao) s.l. and Williriedellum (?) marcucciae Cortese have been extended with respect to those stated in Baumgartner et al. 1995a. Syringocapsidae family is extraordinarily abundant and new morphogroups are presented here: Podobursa sp. A, Podobursa sp. B, Syringocapsa sp. A, Syringocapsa sp. B. Other new morphogroups are: Fultacapsa sphaerica (Ozvoldova) ssp. A, Loopus sp. A, transitional forms between Emiluvia orea Baumgartner and Emiluvia ultima Baumgartner & Dumitrica, transitional forms between Tetratrabs bulbosa Baumgartner and Tetratrabs zealis (Ozvoldova).